2023
DOI: 10.1038/s41467-023-35793-w
|View full text |Cite
|
Sign up to set email alerts
|

CD26-negative and CD26-positive tissue-resident fibroblasts contribute to functionally distinct CAF subpopulations in breast cancer

Abstract: Cancer-associated fibroblasts (CAFs) are abundantly present in the microenvironment of virtually all tumors and strongly impact tumor progression. Despite increasing insight into their function and heterogeneity, little is known regarding the origin of CAFs. Understanding the origin of CAF heterogeneity is needed to develop successful CAF-based targeted therapies. Through various transplantation studies in mice, we show that CAFs in both invasive lobular breast cancer and triple-negative breast cancer originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Supported by our finding that NRF2 and the OSR are high in iCAFs, and since it was suggested that normal fibroblasts likely give rise to iCAFs (Houthuijzen et al , 2023), we hypothesized that NRF2 either regulates the transition of normal fibroblasts to iCAF, the transition from iCAFs to myCAFs, or both. To test this hypothesis, we performed trajectory analysis of two of the scRNA- seq datasets we analyzed, which also contained normal samples of breast and pancreatic tissues (Pal et al , 2021; Peng et al , 2019)(Figure 6F-J,K-O).…”
Section: Resultsmentioning
confidence: 71%
“…Supported by our finding that NRF2 and the OSR are high in iCAFs, and since it was suggested that normal fibroblasts likely give rise to iCAFs (Houthuijzen et al , 2023), we hypothesized that NRF2 either regulates the transition of normal fibroblasts to iCAF, the transition from iCAFs to myCAFs, or both. To test this hypothesis, we performed trajectory analysis of two of the scRNA- seq datasets we analyzed, which also contained normal samples of breast and pancreatic tissues (Pal et al , 2021; Peng et al , 2019)(Figure 6F-J,K-O).…”
Section: Resultsmentioning
confidence: 71%
“…In this work, we utilized scRNA-seq in combination with bulk transcriptome data for systematically analyzing the cell components within the tumor microenvironment of TNBC. Tumorigenesis is governed both by genetically altered tumor cells and non-malignant host cells within the tumor microenvironment, extensively impacting tumor progression, metastases, and therapeutic outcomes [39]. We reported that the tumor microenvironment of TNBC was composed of B cells, dendritic cells, endothelial cells, epithelial cells, fibroblasts, macrophages, monocytes, plasmablasts, and T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other clusters, cluster 4 CAFs were not enriched for "extracellular matrix structural constituent" (Figure 1F), suggesting that cluster 4 CAFs were not the main contributor to ECM (extracellular matrix) structure. Cluster 5 CAFs predominantly expressed cytokine Cxcl12, which is expressed in the iCAF subset and involved in myeloid cell recruitment 23 . Taken together, our data suggest the presence of distinct subsets of CAFs in WT and LATS1/2 dKO breast tumors.…”
Section: Single-cell Rna Sequencing (Scrna-seq) Analysis Reveals Dist...mentioning
confidence: 99%